2014
DOI: 10.1186/1749-799x-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of radiographic findings of femoroacetabular impingement in the Japanese population

Abstract: BackgroundFemoroacetabular impingement (FAI) is one factor known to cause pain and osteoarthritis (OA) of the hips. Although secondary OA due to hip dysplasia is common among Japanese populations, primary OA is seldom observed. Concomitantly, FAI is also thought to be uncommon in Japan, but relatively few epidemiological studies have addressed this issue. This study aimed to clarify the prevalence of radiographic findings of FAI in a Japanese population and to evaluate whether FAI is a risk factor for the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Mori et al [8] identified radiographic evidence of FAI in 29.7 % of patients during an investigation of OA patients with hip pain corresponding to grade 0 or 1 in the Tönnis classification. Meanwhile, Fukushima et al [9] presented radiographic evidence of radiographic FAI in 27.6 % of 87 patients who had undergone total hip arthroplasty, with no pain on the contralateral side, during the procedure in a retrospective examination. Additionally, Takeyama et al [24] reported on the causes of hip OA in Japan.…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…Mori et al [8] identified radiographic evidence of FAI in 29.7 % of patients during an investigation of OA patients with hip pain corresponding to grade 0 or 1 in the Tönnis classification. Meanwhile, Fukushima et al [9] presented radiographic evidence of radiographic FAI in 27.6 % of 87 patients who had undergone total hip arthroplasty, with no pain on the contralateral side, during the procedure in a retrospective examination. Additionally, Takeyama et al [24] reported on the causes of hip OA in Japan.…”
Section: Figmentioning
confidence: 97%
“…A pincer deformity is defined as a morphological abnormality of the acetabular side of FAI, and is characterized by excessive anterior coverage at the superior acetabulum or acetabular retroversion. Many studies have described these radiographic deformities and the prevalence of FAI [3][4][5][6][7][8][9]. However, many of the reports were roentgenogram image investigations, which run the risk of being affected by the patient's position and posture [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, most reports on the prevalence of FAI come from surgical populations and may not represent the prevalence in the general population [2,16,21]. Not only is the prevalence of FAI determined for all the ages, but, from recent studies, it is not yet clear (1) if FAI represents a normal variant or a condition associated with severe and aggressive arthritis; and (2) if this relationship changes with age [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of FAI has been reported to range from 6% to 35%, depending on the criteria of inclusion of the population and the definitions of FAI [16]. In addition, most reports on the prevalence of FAI come from surgical populations and may not represent the prevalence in the general population [2,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior femoroacetabular impingement (FAI), a well-described cause of failure to preserve the re-orientated joint, could be another confounder for the poorer outcome after Bernese periacetabular osteotomy in Western populations. FAI is less prevalent amongst Japanese compared to Caucasians [3,8,9,11] and this could have a positive impact on the chances of preserving the re-orientated joint in this cohort. Future studies will need to address these gaps in our knowledge.…”
mentioning
confidence: 99%